2019
DOI: 10.14735/amko2019252
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspective on HPV-Associated Oropharyngeal Carcinomas and the Role of p16 as a Surrogate Marker of High-Risk HPV

Abstract: 1 I. ústav patologie, LF MU a FN u sv. Anny v Brně 2 Klinika radiační onkologie, LF MU a Masarykův onkologický ústav, Brno 3 CEITEC -Středoevropský technologický institut, MU, Brno 4 Klinika komplexní onkologické péče, LF MU a Masarykův onkologický ústav, Brno SouhrnVýchodiska: Karcinomy orofaryngu asociované s lidským papilomavirem (human papillomavirus -HPV) nejen pro svou nadále vzrůstající incidenci představují významnou kapitolu v oblasti nádorů hlavy a krku. Tyto nádory oproti HPV negativním karcinomům o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…A similar correlation possibly exists, because the esophagus may also be infected with HPV [25]. HPV-infected tumors are characterized by a high expression of p16, which is widely considered as an alternative marker for HPV infection in squamous cell carcinoma [10,12]. In the present study, the expression rate of p16 in ESCC was 30.8%, which was significantly higher than in normal esophageal mucosa.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A similar correlation possibly exists, because the esophagus may also be infected with HPV [25]. HPV-infected tumors are characterized by a high expression of p16, which is widely considered as an alternative marker for HPV infection in squamous cell carcinoma [10,12]. In the present study, the expression rate of p16 in ESCC was 30.8%, which was significantly higher than in normal esophageal mucosa.…”
Section: Discussionsupporting
confidence: 71%
“…In more than 90% of HPV-positive oropharyngeal cancer, p16 was overexpressed. The immunohistochemical evidence of p16 overexpression has been widely used to establish the correlation between HPV carcinogenic activity in cervical cancer and dysplasia [9][10][11]. The immunohistochemical detection of p16 overexpression may serve as a surrogate marker of functionally relevant HPV infection [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…A similar correlation possibly exists, because the esophagus may also be infected with HPV. HPV-infected tumors are characterized by a high expression of p16, which is widely considered as an alternative marker for HPV infection [10,12]. In the present study, the expression rate of p16 in ESCC was 30.8%, which was signi cantly higher than in normal esophageal mucosa.…”
Section: Expression Levels Of P16 Pik3ca Pik3cb and P53 In Escc Samplessupporting
confidence: 43%
“…In more than 90% of HPVpositive oropharyngeal cancer, p16 was overexpressed. The immunohistochemical evidence of p16 overexpression has been widely used to establish the correlation between HPV carcinogenic activity in cervical cancer and dysplasia [9][10]. Several studies have shown that the immunohistochemical detection of p16 overexpression may serve as a surrogate marker of functionally relevant HPV infection [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, compared with the use of histochemical methods to detect HPV DNA, p16 expression can be used as an independent prognostic factor for overall survival and progression-free survival. 12 Then, p16 immunohistochemistry (IHC) in combination with HPV-DNA detection by PCR has been found to be a powerful indicator of clinical outcome in patients with OPSCC using univariate analysis. 7,13 And previous studies have indicated that p16 may enhance the immunogenicity of dendritic cells (DC) by means of Th1 cytokine secretion and cyclin-dependent pathways.…”
Section: Introductionmentioning
confidence: 99%